Adventitial tertiary lymphoid organ classification in human atherosclerosis - Akhavanpoor, Mohammadreza; Gleißner, Christian A.; Akhavanpoor, Hamidreza; Lasitschka, Felix; Dösch, Andreas; Katus, Hugo; Erbel, Christian (Cardiovascular pathology, 2018)
BACKGROUND: Atherosclerosis is a chronic inflammatory disease of the arterial wall. Adjacent to lamina intima lesion progression, a cellular compound develops in the lamina adventitia, defined as tertiary lymphoid organs (TLO) in mice. But in human system, it remains unknown whether these adventitial cellular accumulations represent these highly organized immunological structures. PATIENTS AND METHODS: In this study, we investigated whether the adventitial cellular compounds represent TLOs in 72 human coronary artery samples by immunoenzyme staining. RESULTS: The study showed that the adventitial cellular compound partly represented TLOs in human coronary arteries affected by atherogenesis in patients suffering from ischemic heart disease (56%) or a fatal myocardial infarction (100%), but not dilated cardiomyopathy. In addition, we established a classification for human TLOs, stage I-III, and showed that all stages were present in diseased coronary arteries. The stage of TLOs highly correlated with lesion size as well as plaque instability and rupture, and all patients with a myocardial infarction had stage III. Additionally, there were cellular infiltration and destruction of the lamina media, which were restricted to TLOs next to ruptured plaques in patients with a fatal myocardial infarction. CONCLUSIONS: TLOs are present in patients with a coronary artery disease and highly correlated with lesion size, plaque instability, and rupture. Further studies are needed to investigate whether TLOs might be a specific diagnostic and drug target to modify plaque instability/rupture.